تحليل الخصائص المساحية والشكلية للأودية الموسمية في ولاية سنار, السودان (2000-2018م) باستخدام نظم المعلومات الجغرافية - أحمد حسين, الأمين محمد علي; رابح أحمد, رابح محمد نور; الصديق, حنان عبد الوهاب الأمين (Gezira Journal of Educational Sciences and Humanities, 2026)
هدفت الدراسة إلى إدخال أسلوب معالجة حديث لدراسة الأودية الموسمية وبناء قاعدة بيانات مورفومترية للأودية الموسمية بولاية سنار باستخدام نظم المعلومات الجغرافية. اتبعت الدراسة المنهج الوصفي والتحليلي والمساحي والمورفومتري، واعتمدت على المصادر الأولية عن طريق الملاحظة والزيارات الميدانية والمصادر الثانوية التي تشمل نموذج الارتفاع الرقمي والمرئيات الفضائية والخرائط الطبوغرافية والأبحاث والكتب والمراجع. توصلت الدراسة إلى بناء قاعدة بيانات للخصائص المورفومترية للأودية الموسمية في ولاية سنار، والخروج بمجموعة من الخرائط المورفومترية الخاصة بهذه الأودية، وأظهرت الدراسة وجود تشابه في الخصائص المورفومترية لأحواض أودية العطشان, الرقيق, العزاز, برقو, الوالية بولاية سنار، تختلف مساحة الأحواض فيما بينها بشكل عام وكذلك على مستوى كل رتبة نهرية، وأن متوسط الأحواض يزداد بازدياد الرتبة وأن متوسط محيط الأحواض الفرعية حسب الرتبة لحوض الوادي يزداد كلما تدرجنا في الرتبة، وهنالك تقارب شديد في قيم شكل أحواض الأودية بالمنطقة وأن نسبة الاستطالة تتقارب من الواحد الصحيح في جميع رتب الأحواض وكذلك نسبة تماسك الأحواض، وأن قيم التضرس بالنسبة لهذه الأودية مرتفعة وكذلك قيم الوعورة على مستوى أحواض الرتب. توصى الدراسة بإجراء مزيد من الدراسات التطبيقية المورفومترية للمساهمة في توفير قياسات دقيقة للأودية المجهولة في السودان عامة ومنطقة الدراسة خاصة، ومعرفة الآثار البيئية المترتبة على تغيراتها الجيومرفولوجية، وتوفير الإمكانيات المناسبة لتكون مرجع أو بنك معلومات لكل متخصصي الجيومورفولوجيا والهيدرولوجيا وصناع القرار.         The study aimed to introduce a modern processing technique for studying seasonal valleys in Sinnar State and establishing a morphometric database by using geographical information systems (GIS).  The study followed the descriptive, analytical, and morphometric methods. The research depended on primary data sources, namely observation, and field visits, as well as secondary sources including the Digital Elevation Model, satellite images, typographical maps, research papers, books, and references. The study established a database of morphometric characteristics for seasonal valleys in Sinnar State and produced a set of morphometric maps specific to these valleys. The study revealed similarities in the morphometric characteristics of the basins of Wadi Al-Atshan, Al-Rigeig, Al-Azaz, Bargo, and Al-Walia in Sinnar State. The basins generally vary from one another as well as at the level of each stream order. The findings show that the average area of the basins increases as the higher steam order increases. There is a close similarity in the basin shape values in the region; the elongation ratio approaches (1.0) across all basin orders, as so does the basin compactness ratio. The relief values for these valleys are high, and so are rugosity values at the level of the stream order basins. The study recommends conducting further applied morphometric research to contribute to providing accurate measurements of ungauged wadis in Sudan in general, and the study area in particular. It also emphasizes understanding the environmental impacts resulting from geomorphological changes of the valleys, and providing the adequate means to make such studies serve as a reference or a data bank for geomorphologists, hydrologists, and decision-makers.